2018
DOI: 10.1093/bioinformatics/bty631
|View full text |Cite
|
Sign up to set email alerts
|

SonicParanoid: fast, accurate and easy orthology inference

Abstract: Supplementary data are available at Bioinformatics online.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
128
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 20 publications
1
128
0
Order By: Relevance
“…In these tests, the runtimes of Broccoli were found between those of Sonicparanoid and OrthoFinder2 (Figure 4). Regarding the two extremes of the speed spectrum, OrthoFinder2 with the MSA option was by far the slowest pipeline, and Sonicparanoid, which only performs half of similarity searches (Cosentino and Iwasaki 2019), was found to be the fastest for every dataset. The same speed rank was observed when analysing the QfO 2018 dataset, which contains 78 species, using 8 CPUs: Sonicparanoid (522 minutes), Broccoli (634 minutes) and OrthoFinder2 (850 minutes; we did not test the MSA option using this dataset).…”
Section: Running Time Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In these tests, the runtimes of Broccoli were found between those of Sonicparanoid and OrthoFinder2 (Figure 4). Regarding the two extremes of the speed spectrum, OrthoFinder2 with the MSA option was by far the slowest pipeline, and Sonicparanoid, which only performs half of similarity searches (Cosentino and Iwasaki 2019), was found to be the fastest for every dataset. The same speed rank was observed when analysing the QfO 2018 dataset, which contains 78 species, using 8 CPUs: Sonicparanoid (522 minutes), Broccoli (634 minutes) and OrthoFinder2 (850 minutes; we did not test the MSA option using this dataset).…”
Section: Running Time Analysesmentioning
confidence: 99%
“…Current de novo clustering algorithms are all based on the analysis of pairwise protein distances. Two main approaches have been proposed: distances can be analysed (i) using the best bi-directional hits (BBH) approach or one of its derivative to infer orthologous pairs as implemented in Hieranoid or OMA (Huynen and Bork 1998;Roth, et al 2008;Schreiber and Sonnhammer 2013;Sonnhammer and Ostlund 2015;Cosentino and Iwasaki 2019), or (ii) using the Markov Cluster algorithm (MCL) to infer orthologous groups from the network of similarities (Dongen 2000;Li, et al 2003;Emms and Kelly 2015), orthologous groups that can further be analysed using phylogenetic analyses and a species tree reconciliation approach to infer orthologous pairs (Emms and Kelly 2019). The BBH approach is highly precise but is inclined to miss orthologous pairs due to its highly constrained nature (Dalquen and Dessimoz 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic relationships between two subgroups of L. buchneri and their related species were inferred based on conserved single-copy genes as follows. Protein-coding genes for each genome were (re-)annotated using dfast (version 1.2.2) [35], then clustered into orthologous groups using SonicParanoid (version 1.0) [36]. Each of the identified 964 single-copy orthologues were aligned using muscle (ver 3.8.31) [37], followed by elimination of poorly aligned positions and divergent regions by Gblocks (version 0.91b) [38].…”
mentioning
confidence: 99%
“…QfO service 205 evaluates the predictive quality by performing four phylogeny-based tests of Species Gene Ontology conservation test and Enzyme Classification conservation test[24]. We also applied 210 two more orthology prediction tools, SonicParanoid[47] and InParanoid (v4.1)[4],211 on the QfO 2011 set and used their results as control. The pairwise orthology rela-212 tionships were extracted from the predicted orthologous groups of all the tools, in-213 cluding SonicParanoid and InParanoid, and then submitted to the QfO web-service The homology search results show that BLASTP detected the largest number 228 of homologs (947,203,546).…”
mentioning
confidence: 99%
“…A 43 comparison of several methods that include both tree-based and graph-based meth- 44 ods found that tree-based methods had even a worse performance than graph-based 45 methods on large dataset [10]. One study compared several common methods in- 46 cluding RBH, graph-based and tree-based and found that tree-based methods often 47 give a higher specificity but lower sensitivity [20]. Several studies have also shown 48 that graph-based methods find a better trade-off between specificity and sensitiv- 49 ity than tree-based methods [10,20,21].…”
mentioning
confidence: 99%